2023
DOI: 10.18016/ksutarimdoga.vi.1058856
|View full text |Cite
|
Sign up to set email alerts
|

New Records for the Turkish Freshwater Algal Flora in Twenty Five River Basins of Türkiye, Part I: Bacillariophyta

Abstract: The present study aimed to contribute to the algal flora of Turkey by Bacillariophyta (diatom) as new records for the Turkish freshwater algal flora. Phytobenthos and phytoplankton were sampled three times (spring, summer, and autumn) a year between 2017 and 2019. Samples of the phytoplankton were collected with a water sampler from three depths, and samples of diatoms were obtained as epiphytic in the littoral zone of the lakes. However, if macrophytes were absent, epilithic or epipelic diatoms were sampled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Göğer‐Erdem (2013) has determined the epilithic, epiphytic, and epipelic diatom flora of Lake Köyceğiz. Moreover, Coşkun et al (2023) have reported one new diatom species for Türkiye flora from Lake Gölhisar. Except for paleolimnological studies on diatoms in the lentic systems of the basin (Eastwood et al, 2007), no other studies were reported on lentic littoral diatoms.…”
Section: Introductionmentioning
confidence: 99%
“…Göğer‐Erdem (2013) has determined the epilithic, epiphytic, and epipelic diatom flora of Lake Köyceğiz. Moreover, Coşkun et al (2023) have reported one new diatom species for Türkiye flora from Lake Gölhisar. Except for paleolimnological studies on diatoms in the lentic systems of the basin (Eastwood et al, 2007), no other studies were reported on lentic littoral diatoms.…”
Section: Introductionmentioning
confidence: 99%